2018
DOI: 10.1037/xge0000389
|View full text |Cite
|
Sign up to set email alerts
|

Consequences for peers differentially bias computations about risk across development.

Abstract: Adolescents routinely take risks that impact the well-being of the friends they are with. However, it remains unclear when and how consequences for friends factor into decisions to take risks. Here we used an economic decision-making task to test whether risky choices are guided by the positive and negative consequences they promise for peers. Across a large developmental sample of participants ages 12-25, we show that risky decision computations increasingly assimilate friends' outcomes throughout adolescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 55 publications
2
41
0
Order By: Relevance
“…We found that younger participants exhibited higher levels of risk taking in the hot task because they were less deterred by the probability of incurring the potential loss associated with riskier choices. These results converge with prior work demonstrating greater tolerance of risk in adolescents’ decisions compared to adults’ (Defoe et al., ; Powers et al., ) and further constrains these shifts to affectively engaging contexts such as the hot CCT.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We found that younger participants exhibited higher levels of risk taking in the hot task because they were less deterred by the probability of incurring the potential loss associated with riskier choices. These results converge with prior work demonstrating greater tolerance of risk in adolescents’ decisions compared to adults’ (Defoe et al., ; Powers et al., ) and further constrains these shifts to affectively engaging contexts such as the hot CCT.…”
Section: Discussionsupporting
confidence: 88%
“…We found that the mere presence condition did not yield significantly altered risky choice in either task and at any age. These findings mirror classic and more recent work demonstrating that audience effects on performance are constrained to active monitoring conditions (Cottrell, Wack, Sekerak, & Rittle, 1968;Powers et al, 2018). The present findings imply that the active monitoring by peers is a critical element of the mechanisms that, under certain circumstances, lead to enhanced risky choice with peers in adolescents more so than adults.…”
Section: Mere Presence Of Peerssupporting
confidence: 88%
See 1 more Smart Citation
“…Although this seems surprising at first since adolescents are generally thought to take more risks than adults in the real world and therefore one might expect that adolescents also take more risks than adults in the laboratory, the literature on developmental patterns of risky decision‐making in the laboratory shows mixed results. Some studies have found increased risky decision‐making in adolescence (Braams et al., ; Chein et al., ; Powers et al., ) whereas other studies do not find differences (Blankenstein et al., ; Van Leijenhorst et al., ). Adolescent increases in risk taking behavior in the real world are not only driven by the analysis of objective risk in a situation.…”
Section: Discussionmentioning
confidence: 99%
“…Loss-related processing in the anterior insula has been linked to avoidance learning from punishments (Samanez-Larkin et al ., 2008; Palminteri et al ., 2012), suggesting that insula activity may subserve the ability to use negative outcomes to incrementally update value representations. Though future work is needed to elucidate the behavioral consequences of this trajectory, it stimulates hypotheses about whether attenuated loss value processing is a key mechanism that contributes to adolescents’ tendency toward risky decision-making (Figner et al ., 2009; Defoe et al ., 2015; Powers et al ., in press) and altered learning from or sensitivity to negative feedback (van Duijvenvoorde et al ., 2008; van den Bos et al ., 2012; Rodman et al ., 2017). …”
Section: Discussionmentioning
confidence: 99%